Weeds Ethnobotanical Studies: Use of Midicinal Plant as A Self-Medication by The Community of Bayan Traditional Village, North Lombok District, West Nusa Tenggara - Nihla Farida; I Ketut Ngawit; Ahmad Jupri (Jurnal Penelitian Pendidikan IPA, 2024)
The study aimed to describe and inventory the diversity of medicinal plant species used by the people of Bayan traditional village. The study used descriptive methods and data collection using survey techniques and semi-structured interviews. The survey location was determined by random sampling in the yards of the Sasak, Balinese, and Javanese tribes, each with three sampling points. Parameters observed were population characteristics, morphology, and how to use medicinal plants. The results showed that medicinal plants were found in the yards of the Javanese tribe in 50 species with 1197 individuals, the Balinese tribe in 47 species with 974 individuals, and the Sasak tribe in 35 species with 548 individuals. The dominant species with the highest abundance index were star gooseberry, agathi, turmeric, ginger, white tumeric, halviva, cat's whiskers, and noni. The medicinal plant species found have been used to treat 28 kinds of diseases. The form of plant life that is widely used for medicine is herbaceous. The part of the plant organ that is most widely used for traditional medicine raw materials is the leaf. The most common way to process medicinal plants is by boiling them, then drinking boiled water, finely grinding them, and drinking the juice.